(untitled) (International Journal of Engineering and Computer Science, 2016)
The globalization fact has gained more momentum together with development in free market economy. Together with this new formation, developed countries have opened their doors to competition and have started to take new steps at state-economy relations. While globalization which requires economic, social and political integration of all world countries is creating positive consequences especially in economic and political fields for developed countries, it has brought some negative effects for economies of underdeveloped countries which do not have a substructure proper for such an integration. Contribution of “Competition” and “Innovation” concepts over new economy forms the axis of this study and development of competition and innovation indicators are examined comparatively regarding Turkey and other selected countries.